Thoughts from a Former Editor-in-Chief - LaVelle, Laura (Columbia Journal of Gender and Law, 2000)
I spent more hours working on the Columbia Journal of Gender and Law (JGL) than on any class I ever took at Columbia, but I think it was just as educational an experience as I have had in a classroom. It is a journal whose members take it very personally. On the interview trail, I met one of JGL’s founding members and I told her that the 1996- 1997 JGL board decided to replace the cover illustration with a more traditional table of contents cover. She was really shocked, and a bit shaken up because she had designed the illustration. I remember thinking then that I wished JGL had more of an institutional memory. I felt the same way when I was EIC–so many times I felt we were reinventing the wheel when we tried to sell subscriptions, publicize the journal, change printers, or handle issues with the administration. In the interest of preserving some of JGL’s history, I will explain that the Columbia Women’s History Month Writing Competition was dreamed up by myself and Afra Afsharipour in 1998. Afra was a Submissions Editor for JGL in 1997-1998 as well as the Columbia Law Women’s Association (CLWA) Chair. I was a Production Editor for JGL and the CLWA board member in charge of Women’s History Month. We put out a call for papers, formed a joint committee of JGL and CLWA members, and were overwhelmed at the response. The winners were announced at the Myra Bradwell Day Dinner. I would like to think that we began a tradition that will continue for years.